Enhancing Geographical Indications Product Protection: A Comparative Study of Indonesia and India - Lu Sudirman; Ampuan Situmeang; Fiona Fiona (Journal of Judicial Review, 2023)
Indonesia boasts abundant natural resources, yet its registered Geographical Indication products remain limited compared to India. Despite its strategic geographical location and diverse offerings, many Indonesian Geographical Indication products lack registration and protection. This research conducts a legal comparison of Geographical Indication product protection between Indonesia and India. Utilizing a normative juridical approach and qualitative analysis of secondary legal materials, the study examines Law Number 20 of 2016 concerning Trademarks and Geographical Indications in Indonesia and The Geographical Indications of Goods (Registration and Protection) Act, 1999 in India. The findings reveal that Indonesia lacks a time limit for protection, unlike India, which grants ten renewable years of protection with more stringent sanctions. Considering India's approach, Indonesia should tailor its protection timeframe and penalties to its unique context for optimal results.